2021
DOI: 10.3390/ijerph18189810
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of EEG Characteristics of Drivers and Driving Safety in Undersea Tunnel

Abstract: To study the influence of the driving environment of an undersea tunnel on driver EEG (electroencephalography) characteristics and driving safety, a real vehicle experiment was performed in the Qingdao Jiaozhou Bay Tunnel. The experimental data of the drivers’ real vehicle experiment were collected using an illuminance meter, EEG instrument, video recorder and other experimental equipment. The undersea tunnel is divided into different areas, and the distribution law of driving environment characteristics, EEG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The research in the driving environment also showed that illuminance was positively correlated with the β band. 50 This is consistent with the findings of this study. Also, high-illuminance lights may awaken the central nervous system.…”
Section: Discussionsupporting
confidence: 93%
“…The research in the driving environment also showed that illuminance was positively correlated with the β band. 50 This is consistent with the findings of this study. Also, high-illuminance lights may awaken the central nervous system.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the emotional state of drivers could be assessed by using subjective methods, such as Self-Assessment-Manikin [79] or the Reverse Comic Strip [80]. Physiological parameters are measured based on changes in EEG, ECG, eye movement, and other indicators of drivers [81][82][83][84], indirectly evaluating their psychological loads. Among them, the subjective evaluation method is greatly affected by individual differences and cannot evaluate driving performance and load in real time.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they studied the effect of longitudinal grade on HRG and speed and proposed that the psychological tension of drivers is higher when driving downhill in a tunnel [19]. Yang et al analyzed vehicle speed and drivers' electroencephalography characteristics in the tunnels via a naturalistic driving experiment, which indicated that the drivers' electroencephalography power change rate in the upslope area of tunnels is higher and has the greatest impact on driving safety [20]. Rendon-Velez et al used driving simulation to study drivers' psychological and driving behavior characteristics in tunnels.…”
Section: Introductionmentioning
confidence: 99%